2019
DOI: 10.1158/1541-7786.mcr-18-0836
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor 1 (PAI1) Promotes Actin Cytoskeleton Reorganization and Glycolytic Metabolism in Triple-Negative Breast Cancer

Abstract: Migration and invasion of cancer cells constitute fundamental processes in tumor progression and metastasis. Migratory cancer cells commonly upregulate expression of plasminogen activator inhibitor 1 (PAI1), and PAI1 correlates with poor prognosis in breast cancer. However, mechanisms by which PAI1 promotes migration of cancer cells remain incompletely defined. Here we show that increased PAI1 drives rearrangement of the actin cytoskeleton, mitochondrial fragmentation, and glycolytic metabolism in triple-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 48 publications
1
48
0
2
Order By: Relevance
“…Moreover, in triple negative breast cancer (TNBC), PAI-1-secreted by TNBC cells could stimulate the expression and secretion of CCL5 from endothelial cells, which then enhanced TNBC cells migration, invasion, and metastasis [44]. Overexpression of PAI-1 in TNBC cells further promoted alignment of collagen perpendicular to the margin of tumor, suggesting PAI-1 might exert roles in surrounding tumor microenvironment in orthotopic breast cancer [48]. Interestingly, our present study indicated breast cancer cells secreted PAI-1 led to the activation of PLOD2 expression in adipocytes microenvironment, while the addition of tiplaxtinin further abrogated PLOD2 activation in CAAs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in triple negative breast cancer (TNBC), PAI-1-secreted by TNBC cells could stimulate the expression and secretion of CCL5 from endothelial cells, which then enhanced TNBC cells migration, invasion, and metastasis [44]. Overexpression of PAI-1 in TNBC cells further promoted alignment of collagen perpendicular to the margin of tumor, suggesting PAI-1 might exert roles in surrounding tumor microenvironment in orthotopic breast cancer [48]. Interestingly, our present study indicated breast cancer cells secreted PAI-1 led to the activation of PLOD2 expression in adipocytes microenvironment, while the addition of tiplaxtinin further abrogated PLOD2 activation in CAAs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-1 COLI Regulated to facilitate melanoma cell growth and invasion [227,228] COLIV Regulated to foster breast cancer cell invasion in response to prolactin [229] MMP-2 COLI Modulating MMP-2 activation in osteosarcoma [230] COL4A2 Modulating MMP-2 activation and activity in liver cancer [231] COLI and COLIV Regulated by the knockdown of MMP-2 to induce cancer metastases [232,233] Collagen organization Regulated to enhance malignant glioma recurrence and resistance to vemurafenib [234,235] MMP carcinoma [166,167]. TACS-3 was shown to be driven by increased plasminogen activator inhibitor 1 via ERK signaling and promoted the migration of triple-negative breast cancer cells [168]. The elevated density and depth of collagen deposition showed high proliferation and invasion of cancer cells [169,170].…”
Section: Subtype Of Mmps Associated Collagen Pathological Functions Omentioning
confidence: 99%
“…To identify the activity of ERK and Akt, we used the kinase translocation reporter (KTR) for ERK and Akt as previously described [17,18]. This KTR construct contains H2B fused to mCherry (H2B-mCherry), the Akt-KTR reporter (Aquamarine), the ERK-KTR reporter (mCitrine), and a puromycin selection marker all separated by P2A linker sequences cloned into the Piggyback transposon vector as described previously (pHAEP) [18].…”
Section: Vectors and Cell Linesmentioning
confidence: 99%